Creating the need to access peer knowledge: Changing the learning culture in teacher education through learning design - Dobozy, Eva (e-JBEST, 2012)
Over the years, traditional teacher-centric and content driven teaching explanations in textbooks and unit outlines have been infused with studentcentric pedagogical descriptors. How these rhetorical changes have affected teaching and learning habits in teacher education is what is under investigation in this paper. The findings of this exploratory study suggest that learning design can enable greater peer collaboration and interaction. However, the increased interaction does not necessarily equate to deeper processing of information. The conclusion is reached that unless the value-added nature of increased peer interaction and collaborative inquiry is better understood by teacher educators and student teachers; it is unlikely that habitual learning behaviours will change.